Self‐Assembly of Highly Stable Zirconium(IV) Coordination Cages with Aggregation Induced Emission Molecular Rotors for Live‐Cell Imaging. (23rd January 2020) - Dong, Jinqiao; Pan, Yutong; Wang, Heng; Yang, Kuiwei; Liu, Lingmei; Qiao, Zhiwei; Yuan, Yi Di; Peh, Shing Bo; Zhang, Jian; Shi, Leilei; Liang, Hong; Han, Yu; et al.
Abstract: The self‐assembly of highly stable zirconium(IV)‐based coordination cages with aggregation induced emission (AIE) molecular rotors for in vitro bio‐imaging is reported. The two coordination cages, NUS‐100 and NUS‐101, are assembled from the highly stable trinuclear zirconium vertices and two flexible carboxyl‐decorated tetraphenylethylene (TPE) spacers. Extensive experimental and theoretical results show that the emissive intensity of the coordination cages can be controlled by restricting the dynamics of AIE‐active molecular rotors though multiple external stimuli. Because the two coordination cages have excellent chemical stability in aqueous solutions (pH stability: 2–10) and impressive AIE characteristics contributed by the molecular rotors, they can be employed as novel biological fluorescent probes for in vitro live‐cell imaging. Abstract : Hochstabile Koordinationskäfige mit dreikernigen Zirkonium‐Eckpunkten und flexiblen, mit Carboxylgruppen ausgestatteten Tetraphenylethylen(TPE)‐Abstandshaltern wurden durch Selbstassemblierung gebildet. Die beiden wasserstabilen Käfige weisen beeindruckende Eigenschaften in der aggregationsinduzierten Emission (AIE) auf, die von den molekularen Rotoren eingebracht werden, und können als biologische Fluoreszenzsonden für Lebendzell‐Bildgebung eingesetzt werden.